Rethinking foodscapes: How agricultural pollution threatens biodiversity and what we can do about it - CGIAR Multifunctional Landscapes (CGIAR System Organization, 2025)
Agricultural pollution is an increasingly significant driver of biodiversity loss across food, land, and water systems. This article examines how nutrient runoff, pesticide use, and other agricultural pollutants degrade ecosystems, threaten species diversity, and undermine the sustainability of food production. Drawing on scientific evidence and case examples, the piece explores the pathways through which agricultural pollution affects soils, freshwater systems, and surrounding landscapes. It also outlines practical and policy-relevant strategies to mitigate these impacts, including nature-positive farming practices, improved nutrient management, and integrated landscape approaches. The article underscores the need to rethink foodscapes as multifunctional systems, where agricultural productivity is balanced with ecosystem health, biodiversity conservation, and long-term resilience.